Returning home empty handed: Examining how COVID-19 exacerbates the non-payment of temporary migrant workers' wages. (December 2021) - Foley, Laura; Piper, Nicola
The crisis unleashed by COVID-19 has profoundly impacted the world of work, with many workers losing their jobs or with insufficient safety measures in place for those still in work. Migrant workers are among the precarious workforce that is employed in particularly affected sectors where they have been subjected to labour rights' violations for a long time. The pandemic has further exposed and exacerbated the exploitation of migrant workers in particular, as evident from the widespread occurrence of the non- or underpayment of wages for work that has been carried out. Despite the efforts made in recent years at the global level to arrive at a common framework to regulate international labour migration in accordance with international human and labour rights' standards, little progress has been achieved on the issue of wage theft. This article analyses the reasons why the institutional architecture in place is ineffective to tackle the settlement of outstanding wage claims. We use the concept of access to justice as a starting point and steer our examination towards global advocacy as epitomised by a concerted campaign by an alliance between civil society organisations (CSOs) and global union confederations, which calls for the implementation of a justice mechanism for repatriated migrant workers. Our analysis is specifically centred on low-wage migrants on temporary, employer-tied contracts as illustrated by the South Asia–Middle East/Gulf migration corridor.